The Probiotic Biosurfactant From Levilactobacillus brevis Strain F20 Isolated from a Diary Product with Potential Food Applications. Issue 4 (2nd October 2022) - Soleiman Meiguni, Fatemeh; Imanparast, Somaye; Salimi, Fatemeh; Nemati, Fahimeh
ABSTRACT: In recent years, probiotic bacteria have received considerable attention for biosurfactant (BS) production. In the current study, 80 bacteria were isolated from 70 dairy samples. F20 isolate was selected based on probiotic tests and identified by 16S rRNA method as Levilactobacillus brevis and introduced as valuable candidate for producing biosurfactant. The results of optimization by Central Composite Design (CCD) showed the maximal biosurfactant production at 2.75% of glucose, 3.625% of oil, and 4.25% of yeast concentration. The emulsification index E24 values of 17.14% and 37.5% were obtained in the presence of hexadecane and crude oil, respectively and the biosurfactant production by L. brevis decreased surface tension to 38.05 mN/m. The results obtained TLC and FTIR analysis have confirmed the presence of glycolipid and lipopeptide moieties in the structure of BS. This research indicated that L. brevis strain F20 could be a promising biosurfactant producer in the food and medicine industries.